2010
DOI: 10.1080/09585176.2010.529637
|View full text |Cite
|
Sign up to set email alerts
|

‘Schools and Continuing Professional Development in England – State of the Nation’ research study: policy context, aims and design

Abstract: This article introduces the Schools and Continuing Professional Development State of the Nation study (SoNS). Discussion of English policy together with an account of the study's aims and research design provide a context for the other articles included in this special issue. A key assumption behind the research, and the prevailing CPD policy context in England, is that organisational conditions in schools are highly influential in the development of sustained and effective classroom‐based, collaborative, inqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 20 publications
5
38
0
Order By: Relevance
“…We see little differentiation between primary schools with middling achievement and those with low achievement. This supports the overall finding from the Schools and continuing professional development (CPD) in England -State of the nation research project (Pedder et al 2009) that schools tend to have low levels of support for the professional learning of teachers. In this instance, only high performing primary schools appear to have the kinds of school influences most associated with continuous teacher professional learning.…”
Section: School Learning Factors and School Achievementsupporting
confidence: 71%
See 1 more Smart Citation
“…We see little differentiation between primary schools with middling achievement and those with low achievement. This supports the overall finding from the Schools and continuing professional development (CPD) in England -State of the nation research project (Pedder et al 2009) that schools tend to have low levels of support for the professional learning of teachers. In this instance, only high performing primary schools appear to have the kinds of school influences most associated with continuous teacher professional learning.…”
Section: School Learning Factors and School Achievementsupporting
confidence: 71%
“…That is, teachers in the middling to the lowest performing secondary schools reported very similar, low levels of learning activity effectiveness. Again, this is consistent with the general pattern found in the Schools and continuing professional development (CPD) in England -State of the nation research project (Pedder et al 2009) showing that teachers engage in very little professional development that could be considered effective at improving teaching and learning. …”
Section: Professional Learning Activities and School Achievementsupporting
confidence: 71%
“…A recent large-scale study into the nature of CPD practices in schools in England (which had 1126 responses) found individual, isolated workshop approaches typify teachers' learning practices, many of which were associated with compliance with specific government priorities (Pedder, Storey, & Opfer, 2008). Similarly, Hustler, McNamara, Jarvis, Londra and Campbell (2003) reveal how 72% of 2259 survey respondents believed too many PD days in England were driven by national foci.…”
Section: The Literature: Understanding Current Conditions Of Teacher mentioning
confidence: 99%
“…Such a stance reveals teachers also simultaneously engage in more ongoing, productive and substantive learning initiatives, thereby challenging narrower managerial approaches. In England, for example, a large scale review of relevant literature found that 11% of teachers undertook university accredited courses (Pedder et al, 2008). Pickering et al (2007) also reveal how teachers' collaboration in a Master's programme offered through the University of London led to teachers being more readily able to critique their own practices.…”
Section: The Literature: Understanding Current Conditions Of Teacher mentioning
confidence: 99%
“…The recommendation in their study is to link individuals' development to the analysis of needs through performance management and career development as well as self-evaluation and school improvement. Pedder, Storey and Opfer (2008) concur, arguing for a symbiotic approach that integrates strands of teachers' development, characterised by a strong correlation between performance management processes and opportunities for continuing professional development (in Walker, et al, 2011). However, Storey (2009) argues that the links between each of these strands are not yet fully understood and require further investigation.…”
Section: Introductionmentioning
confidence: 99%